THE CONSTRUCTION OF IDENTITIES IN EDUCATIONAL ENVIRONMENT - Mauro Giffoni Carvalho (Editora da Universidade de Santa Cruz do Sul, 2012)
In this study are presented some psychosocial considerations concerning adolescent identity construction in the educational environment. As we will see, in this construction process, they take possession of different information and social experiences sources, which face them within the school culture. The identities are closely linked to categories such as the social class, gender, ethnicity, race, sexuality, age besides other categories present in social relations. Schools must undertake in their daily life, as recommend the PCNs (National Curriculum Guidelines, 1997), a reflection about the multiple identities and citizenships, necessary for building a democratic society. The cultural plurality of schools confirms diversity as a key element to the construction of identities, negotiated and defined through conflicts and countless possibilities of singularity.